Ethically Allocating COVID-19 Drugs Via Pre-approval Access and Emergency Use Authorization. Issue 9 (1st September 2020) - Webb, Jamie; Shah, Lesha D.; Lynch, Holly Fernandez
Abstract: Allocating access to unapproved COVID-19 drugs available via Pre-Approval Access pathways or Emergency Use Authorization raises unique challenges at the intersection of clinical care and research. In conditions of scarcity, prioritization approaches should minimize harm, maximize benefit, and promote fairness. To promote continued data collection, patients seeking access to unproven COVID-19 drugs should receive lower priority for allocation when they decline to participate in clinical trials, either of the requested drug or other investigational products, offering a comparable balance of risks and benefits; special attention should be paid to concerns of voluntariness and distrust. In addition, institutional treatment protocols that can contribute more robust real world data should be preferred to single patient requests for access, with priority for inclusion based on traditional clinical allocation criteria relying on available evidence. Fairness demands distribution of these protocols across a diverse range of sites, particularly those serving marginalized populations, among other protections.